Moral Education: Aligning the Essence of Human Creation with the Purpose of Islamic Education - Shalsabila Diah Fasha; Nasikhin; Fihris (Publikasi Inspirasi Indonesia, 2025)
Moral education is an important part of Islamic education which aims to shape human character in accordance with the purpose of its creation by Allah SWT. This article explains how moral education helps humans to understand and carry out their role as noble beings. Moral education not only teaches knowledge, but also instills good values such as honesty, patience, responsibility, and respect for others. With moral education, humans are expected to be able to live in the right way, maintain good relationships with God and fellow humans, and face various challenges in life with a positive attitude. This article also emphasizes that the purpose of Islamic education is not only to develop intelligence, but more importantly to form a good personality and noble character. Therefore, moral education is a very important foundation for humans to achieve happiness in this world and the hereafter. Through this understanding, it is hoped that educators and the public will be more aware of the importance of moral education in forming a morally and spiritually strong generation.